Correlation study between facet joint cartilage and intervertebral discs in early lumbar vertebral degeneration using T2, T2* and T1ρ mapping. - Yi Zhang (PLoS ONE, 2017)
Recent advancements in magnetic resonance imaging have allowed for the early detection of biochemical changes in intervertebral discs and articular cartilage. Here, we assessed the feasibility of axial T2, T2* and T1ρ mapping of the lumbar facet joints (LFJs) to determine correlations between cartilage and intervertebral discs (IVDs) in early lumbar vertebral degeneration. We recruited 22 volunteers and examined 202 LFJs and 101 IVDs with morphological (sagittal and axial FSE T2-weighted imaging) and axial biochemical (T2, T2* and T1ρ mapping) sequences using a 3.0T MRI scanner. IVDs were graded using the Pfirrmann system. Mapping values of LFJs were recorded according to the degeneration grades of IVDs at the same level. The feasibility of T2, T2* and T1ρ in IVDs and LFJs were analyzed by comparing these mapping values across subjects with different rates of degeneration using Kruskal-Wallis tests. A Pearson's correlation analysis was used to compare T2, T2* and T1ρ values of discs and LFJs. We found excellent reproducibility in the T2, T2* and T1ρ values for the nucleus pulposus (NP), anterior and posterior annulus fibrosus (PAF), and LFJ cartilage (intraclass correlation coefficients 0.806-0.955). T2, T2* and T1ρ mapping (all P<0.01) had good Pfirrmann grade performances in the NP with IVD degeneration. LFJ T2* values were significantly different between grades I and IV (PL = 0.032, PR = 0.026), as were T1ρ values between grades II and III (PL = 0.002, PR = 0.006) and grades III and IV (PL = 0.006, PR = 0.001). Correlations were moderately negative for T1ρ values between LFJ cartilage and NP (rL = -0.574, rR = -0.551), and between LFJ cartilage and PAF (rL = -0.551, rR = -0.499). T1ρ values of LFJ cartilage was weakly correlated with T2 (r = 0.007) and T2* (r = -0.158) values. Overall, we show that axial T1ρ effectively assesses early LFJ cartilage degeneration. Using T1ρ analysis, we propose a link between LFJ degeneration and IVD NP or PAF changes.